Development of Socioscientific Issue-Based Interactive E-Modules to Improve Students Critical Thinking Skills on Global Warming Issues - Ummul Uslima; Sunyono Sunyono; Dewi Lengkana (FKIP Universitas Lampung, 2023)
This development research aims to develop and validate interactive e-modules based on socio scientific issues on Global Warming material to improve students' critical thinking skills. This study uses the Research and Development method with 4D design (Define, Design, Develop, Disseminate). The results of construct validation get a score of 85.3 and the feasibility of the material gets a score of 88.2 with the final conclusion